Are consumers leaning towards hedonic, symbolic or functional attributes ? Brand benefits scale development and validation in emerging markets: case of Tunisia - (:unkn) unknown (My University, 2017)
Branding is an important part of consumer decision making whether domestically or internationally. Brand choices are the reflection of consumers’ motivations. Given the importance of branding to international marketers, its role has been studied in different markets developed as well as developing economies. However, most of the studies have focused on developed economies without taking into consideration the value of branding in less developed economies. The North African Market is a market that has been neglected in such research. This study seeks to understand brands benefits in the Tunisian market. The purpose of this study is to develop a psychometric scale measuring brand benefits in Tunisia. The scale development is based on Churchill’s paradigm. Results show that brand benefits converge towards a two-factor structure consisting in a functional and symbolic factor. Since the choice of a brand reflects the motivations an individual seeks to satisfy through its possession, marketing managers could use such a scale to measure the benefits associated with the brands they commercialize in a north-african environment.
Keywords: African Research